Rancang Bangun Solar Dryer untuk Meningkatkan Kualitas Refuse Derived Fuels (RDF) sebagai Bahan Bakar Alternatif di Kiln Burner Industri Semen - Maulida Okta Arifianti, Qurrotin Ayunina; Abidin, Muhammad Rizal; Nugrahani, Elita Fidiya; Ummatin, Kuntum Khoiro (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2018)
To utilize the municipal solid waste (MSW), PT Semen Indonesia has a program to convert waste into three useful products. One of the product is named Refuse Derived Fuel (RDF). The RDF has claimed that it had a caloric value about 5178 kcal/kg. However, currently, RDF could not be used for the combustion process in the cement kiln since RDF has higher moisture content and lower caloric value. In this research, a solar dryer with greenhouse type is designed to reduce the moisture content. The performance is tested using two variations and compared to the conventional method. The variations are a solar dryer with one fan and with no fan. The general results show that variation with one fan has the highest drying rate among all. There is a significant reduction of moisture content after drying process using a solar dryer. The moisture content could be reduced to 16.25 % and 17 % using one fan and no fan, respectively. Furthermore, variation with 1 fan has higher solar dryer efficiency than that of one fan.